Should we eat meat? : evolution and consequences of modern carnivory - Smil, Vaclav (Wiley, 2013)
This book is a wide-ranging and interdisciplinary examination and critique of meat consumption by humans, throughout history and around the world. Setting the scene with a chapter on meat's role in human evolution and it's growing influence during the development of agricultural practices, the book goes on to examine modern production systems, their costs, efficiencies and outputs. The major global trends of meat consumption are described: what part does meat play in changing modern diets in countries around the world? The heart of the book addresses the consequences of the "massive carnivory."